'The world outside seemed mummified into a sheet of dead whiteness': Epiphanic experience in the short stories of Chimamanda Ngozi Adichie. Issue 1 (1st April 2014) - Eilittä, Leena Hannele
This article argues that the female characters in C. N. Adichie's short story collection The Thing Around Your Neck (2009) go through mental developments similar to epiphanic experience as recently defined by Matthew G. McDonald. The characters, who are often living in the diaspora, feel themselves trapped between their African background and influences from the West. While reflecting upon their situation, they gradually acquire a better view of their problems that allows them to distance themselves from their present circumstances and envision a future that would better satisfy their needs. Adichie depicts these mental developments through subtle literary devices that benefit from narrative experiments, words from Igbo vocabulary and devices known from African storytelling traditions.